(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2010)
India is also a complex market that needs careful understanding: It has both old money and new money(and even the new money is subdivided into the entrepreneurial class, the class of executives and the brand-loving baby boomers of the call cetres), as also pronounced by seasonal trends in luxury-brand shopping.The market for luxury goods in India is pegged at 500 illion by a report jointly drafted by FICCI and market search fim1 Ogilvy. The market is likely to grow with luxury services adding 800 million. according to a report byanagement consultancy fim1 A.T. Kearney. the Indian xury assets market is an impressive 2 billion. according same survey. A report by retail consultant Technopak has